High efficiency and clinical relevance of exome sequencing in the daily practice of neurogenetics. Issue 5 (5th March 2021) - Thomas, Quentin; Vitobello, Antonio; Tran Mau-Them, Frederic; Duffourd, Yannis; Fromont, Agnès; Giroud, Maurice; Daubail, Benoit; Jacquin-Piques, Agnès; Hervieu-Begue, Marie; Moreau, Thibault; Osseby, Guy-Victor; Garret, Philippine; et al.
Abstract : Objective: To assess the efficiency and relevance of clinical exome sequencing (cES) as a first-tier or second-tier test for the diagnosis of progressive neurological disorders in the daily practice of Neurology and Genetic Departments. Methods: Sixty-seven probands with various progressive neurological disorders (cerebellar ataxias, neuromuscular disorders, spastic paraplegias, movement disorders and individuals with complex phenotypes labelled 'other') were recruited over a 4-year period regardless of their age, gender, familial history and clinical framework. Individuals could have had prior genetic tests as long as it was not cES. cES was performed in a proband-only (60/67) or trio (7/67) strategy depending on available samples and was analysed with an in-house pipeline including software for CNV and mitochondrial-DNA variant detection. Results: In 29/67 individuals, cES identified clearly pathogenic variants leading to a 43% positive yield. When performed as a first-tier test, cES identified pathogenic variants for 53% of individuals (10/19). Difficult cases were solved including double diagnoses within a kindred or identification of a neurodegeneration with brain iron accumulation in a patient with encephalopathy of suspected mitochondrial origin. Conclusion: This study shows that cES is a powerful tool for the daily practice of neurogenetics offering an efficient (43%) and appropriate approach for clinically and genetically complex and heterogeneous disorders.